PENENTUAN CIRI-CIRI PLAGIARISME DALAM MAKALAH ILMIAH YANG MEREFERENSI SUMBER DALAM BAHASA ASING YANG DITERJEMAHKAN - Michael Iskandar (Center for Economic Studies Universitas Katolik Parahyangan, 2009)
Whenever lecturers assign their students to write scientific papers they must be alert to the plagiarism problem. While a lot has been written about plagiarism, particularly by university policymakers, none address the problem when a student paraphrases and translates one or more passages from sources written in a foreign language. This paper strives to find an answer whether this form of plagiarism or not. In particular, the research strives to find the answer of the following question: what are the characteristics of plagiarism between languages?. Preliminary and superficial research has shown that there are three main aspects that many sources address; the definition of plagiarism, the types of plagiarism, and the characteristics of plagiarism. This research is then done by studying and compiling from those various sources, and then analyzing each aspect separately. To these was added an analysis on the ethical principles that underlie human behavior, with which the insistence that plagiarism is wrong may be validated. The conclusions of this research are that (a) plagiarism is most strongly described as a kind of fraud, not a kind of theft; (b) none of the ethical principles evaluated separately is strong enough to deter plagiarism; (c) there are types of plagiarism that aren't relevant in a discussion on undergraduate scientific paper writing; and (d) if a translated passage is translated back into its original language, and the result is the same or very similar to the original text, then plagiarism has occurred.